Geochemistry and formation of ferromanganese crusts and associated mineral deposits in the Rio Grande Rise, Southwest Atlantic Ocean - Benites, Mariana (2023)
The increasing demand for critical and strategic metals has driven attention to deep-sea mineral deposits as an alternative supply for high-technology industries. Oceanic elevations are important target areas for ferromanganese (FeMn) crust deposits, which are extremely enriched in rare metals including Co, Te, Mo, Bi, Pt, W, Zr, Nb, Y, and rare earth elements (REE). The Rio Grande Rise (RGR) is one of the most extensive oceanic elevations in the South Atlantic Ocean, but its seafloor mineral deposits were poorly investigated until recently. This thesis investigates the genesis and evolution of FeMn crusts from the summit (600 m) to abyssal water depths (> 5000 m) in a wide range of locations in the RGR, but also investigates associated minerals such as phosphorites and ironstones. For this, a suite of mineralogical, chemical, and isotopic analytical techniques were applied. FeMn crusts from RGR differ significantly, whether they come from the summit or from deep water. FeMn crusts from the summit present dual structures, with most of their volume comprising old phosphatized crusts covered by thin young non-phosphatized crusts. As a result, FeMn crusts from the summit bear a diagenetic signature with P, Ni, Li, and Y enrichment and Co, REE, Mo, and Zr depletion. On the other hand, deep-water FeMn crusts (> 2000 m) are entirely hydrogenetic and enriched in As, Be, Co, Cu, Mo, Sb, Se, Ti, Th, Tl, U, Zn, and REE. FeMn crusts most likely started to form in the RGR about 47 Ma. Phosphatization occurred throughout the Miocene, reflecting important climatic shifts such as the Middle Miocene Climatic Optimum, when enhanced surface biological productivity occurred. Especially the crusts shallower than 1500 m were phosphatized, due to proximity to the oxygen minimum zone, a large reservoir for P. The major controls on the observed variations of chemical composition of crusts with water depth are water masses oxygenation, nutrients and paleoproductivity. Regarding the ironstones, a hypothesis for their origin involving Fe oxidizing bacterial mats and a low-temperature geothermal fluid is proposed. This thesis contributed to filling the knowledge gap on baseline information for future mining activities in the RGR and to understanding the controls of modern and past oceanographic conditions on FeMn crust composition, to better target specific crust characteristics.